Plasma Prekallikrein: Its Role in Hereditary Angioedema and Health and Disease - Schmaier, Alvin H. (Frontiers in Medicine, 2018)
Plasma prekallikrein has a critical role in acute attacks of HAE. Unlike C1 inhibitor its levels fall during HAE attacks with resultant cleaved high molecular weight kininogen. Cleavage of high molecular weight kininogen liberates bradykinin, the major biologic peptide that promotes the edema. How prekallikrein initially becomes activated in acute attacks of HAE is not known. Plasma prekallikrein itself is negatively associated with cardiovascular disease. High prekallikrein is associated with accelerated vascular disease in diabetes and polymorphisms of prekallikrein that reduce high molecular weight kininogen binding are associated with protection from cardiovascular events. Prekallikrein deficient mice have reduced thrombosis risk and plasma kallikrein inhibition is associated with reduced experimental gastroenterocolitis and arthritis in rodents. In sum, prekallikrein and its enzyme plasma kallikrein are major targets in HAE providing much opportunity to improve the acute and chronic management of HAE. Plasma kallikrein inhibition also may be a target to ameliorate cardiovascular disease, thrombosis risk, and inflammation as in enterocolitis and arthritis.